Comparative chloroplast genomics and insights into the molecular evolution of Tanaecium (Bignonieae, Bignoniaceae) - Annelise Frazão; Verônica A. Thode; Lúcia G. Lohmann (Scientific Reports, 2023)
Abstract Species of Tanaecium (Bignonieae, Bignoniaceae) are lianas distributed in the Neotropics and centered in the Amazon. Members of the genus exhibit exceptionally diverse flower morphology and pollination systems. Here, we sequenced, assembled, and annotated 12 complete and four partial chloroplast genomes representing 15 Tanaecium species and more than 70% of the known diversity in the genus. Gene content and order were similar in all species of Tanaecium studied, with genome sizes ranging between 158,470 and 160,935 bp. Tanaecium chloroplast genomes have 137 genes, including 80–81 protein-coding genes, 37 tRNA genes, and four rRNA genes. No rearrangements were found in Tanaecium plastomes, but two different patterns of boundaries between regions were recovered. Tanaecium plastomes show nucleotide variability, although only rpoA was hypervariable. Multiple SSRs and repeat regions were detected, and eight genes were found to have signatures of positive selection. Phylogeny reconstruction using 15 Tanaecium plastomes resulted in a strongly supported topology, elucidating several relationships not recovered previously and bringing new insights into the evolution of the genus.